Advanced finite element cross-country ski boot model for mass optimization directions considering flexion stiffness - Hladnik, J.; Jerman, B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
Flexion stiffness and mass were recognized as two important parameters of energy efficiency for modern top-class ski boots used in skate cross-country skiing. This article summarizes the study on mass optimization of the front foot region of an existing cross-country ski boot, while considering its flexion stiffness. For this purpose, a finite element model of the boot and an artificial foot for simulation of boot flexion stiffness measurement were made. The boot consists of textiles which require specific measurements for their characterization and special finite element material models for their realization. The finite element model was validated through a three-step validation process, in which flexion stiffness of the complete and stripped versions of the finite element model were compared with experimentally acquired flexion stiffness. Flexion stiffness contributions of individual boot components of the front foot region were acquired from the strain energy accumulated in their finite element. Using flexion stiffness and mass contributions and ratios between them (flexion stiffness to mass contributions), directions for flexion stiffness to mass contribution optimization of the boot' front region were determined. The shoe-upper and shoe-cap were the most efficient regarding their flexion stiffness to mass contribution ratios and were suggested to be thickened. The soles had the highest potential for the boot's flexion stiffness to mass contribution optimization due to their high mass contribution and relatively low flexion stiffness to mass contribution ratios. As a result, recommendations were made to reduce the soles' size and/or increase their flexion stiffness to mass contribution ratios. These recommendations are similar to recommendations from a previous study, despite the higher finite element model accuracy and different method used to determine the flexion stiffness contributions.